In Vitro and In Vivo Effects of Conventional and Chitosan Nanoparticle-Encapsulated Miltefosine Drug for Treatment of Cutaneous Leishmaniasis - Rahat Ullah Khan; Momin Khan; Qudrat Ullah; Muhammad Zahoor Khan; Aamir Sohail; Rehmat Islam; Hazrat Bilal; Shakeeb Ullah; Aamir Iqbal (Medical Sciences Forum, 2023)
This study aimed to formulate polymer-based chitosan nanoparticles as a drug (miltefosine) delivery system for treating leishmaniasis. Miltefosine-loaded chitosan nanoparticles (MLCNPs) have been synthesized and then characterized by the use of UV-visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), the zeta potential, drug loading content (DLC), encapsulation efficacy (EE) and the dynamic light scattering technique (DLS). Further, the in vitro anti-leishmanial activity of the characterized chitosan nanoparticles was assessed by a microculture tetrazolium (MTT) assay, and in vivo efficacy was evaluated in infected BALB/c mice. The lesion healing was statistically analyzed using Wilcoxon signed-rank and Mann–Whitney tests. The MLCNPs were spherical-shaped (97.5 nm), which presented efficient encapsulation (97.56%), drug loading content (91.5 µg/mL) and a positive surface charge (+1.04 mV). MLCNPs were less hemolytic (6%) when compared to conventional miltefosine. MLCNPs (50 µg/mL) showed a potential antileishmanial effect (mean viability: 10 ± 0.3%) on promastigotes in comparison to conventional miltefosine (mean viability: 18 ± 1.3%). The IC50 value for MLCNPs and miltefosine was 0.0218 µg/mL and 0.3548 µg/mL, respectively. This in vivo study proved that lesions of mice treated with oral and intralesional-injected MLCNPs significantly heal (p = 0.01). MLCNPs have a significant antileishmanial effect and could be utilized as an alternative treatment for CL.